Association between the ABCC11 gene polymorphism-determined earwax properties and external auditory canal microbiota in healthy adults - Yasunobu Amari; Masahiro Hosonuma; Takuya Mizukami; Junya Isobe; Yuki Azetsu; Eiji Funayama; Yuki Maruyama; Toshiaki Tsurui; Kohei Tajima; Aya Sasaki; Yoshitaka Yamazaki; Ryota Nakano; et al. (Microbiology Spectrum)
ABSTRACT The concept of genome–microbiome interactions, in which the microenvironment determined by host genetic polymorphisms regulates the local microbiota, is important in the pathogenesis of human disease. In otolaryngology, the resident bacterial microbiota is reportedly altered in non-infectious ear diseases, such as otitis media pearls and exudative otitis media. We hypothesized that a single-nucleotide polymorphism in the ATP-binding cassette sub-family C member 11 (ABCC11) gene, which determines earwax properties, regulates the ear canal microbiota. We analyzed ABCC11 gene polymorphisms and ear canal microbiota in healthy individuals to understand the relationship between genome–microbiome interactions in the ear canal. The study included 21 subjects who were divided into two groups: 538GA (9) and 538AA (12). Staphylococcus auricularis and Corynebacterium spp. were observed in the 538GA group, whereas Methylocella spp. was observed in the 538AA group. PICRUSt analysis revealed significant enrichment of certain pathways, such as superpathway of N-acetylglucosamine, N-acetylmannosamine and N-acetylneuraminate degradation, chlorosalicylate degradation, mycothiol biosynthesis, and enterobactin biosynthesis in the GA group, whereas allantoin degradation IV (anaerobic), nitrifier denitrification, starch degradation III, L-valine degradation I, and nicotinate degradation I were significantly enriched in the AA group. The ABCC11 gene polymorphism regulates the composition of the ear canal microbiota and its metabolic pathways. This study revealed a genome–microbiome interaction within the resident microbiota of the external auditory canal that may help to elucidate the pathogenesis of ear diseases and develop novel therapies.IMPORTANCEThe ABCC11 gene polymorphism, which determines earwax characteristics, regulates the composition of the ear canal microbiota and its metabolic pathways. We determined the presence of genome–microbiome interactions in the resident microbiota of the ear canal. Future studies should focus on ABCC11 gene polymorphisms to elucidate the pathogenesis of ear diseases and develop therapeutic methods.